Horizontal gene transfer via OMVs co-carrying virulence and antimicrobial-resistant genes is a novel way for the dissemination of carbapenem-resistant hypervirulent Klebsiella pneumoniae - Li, Ping; Luo, Wanying; Xiang, Tian-Xin; Jiang, Yuhuan; Liu, Peng; Wei, Dan-Dan; Fan, Linping; Huang, Shanshan; Liao, Wenjian; Liu, Yang; Zhang, Wei (Frontiers in Microbiology, 2022)
Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-HvKP) has been reported across Asian countries, seriously threatening human health. The rapidly increased isolation rate of CR-HvKP worldwide has brought great difficulties in controlling clinical infection. Moreover, it has been demonstrated that the transmission of drug-resistant genes among bacteria can be mediated by outer membrane vesicles (OMVs), which is a new way of horizontal gene transfer (HGT). Previous reports have indicated that DNA is incorporated into the lumen of OMVs and conveyed to recipient cells. Besides, OMVs derived from K. pneumoniae participate in HGT, facilitating the pervasion of resistance genes in bacterial communities. The transmission of virulence genes among bacteria has also been well studied; however, it remains unclear whether virulence and drug-resistant genes can be co-transmitted simultaneously. Co-transmission of virulence and drug-resistant genes is essential for the formation and prevalence of CR-HvKP. The present study found that Klebsiella pneumoniae could co-deliver virulence and drug-resistant genes via CR-HvKP OMVs. First, we isolated OMVs from CR-HvKP by cushioned-density gradient ultracentrifugation (C-DGUC). We discovered that CR-HvKP OMVs were enriched in the genetic elements of bacteria. OMV-mediated transformation indicated that these CR-HvKP OMVs contained virulence and antimicrobial-resistant genes, which could be transferred from CR-HvKP horizontally to the K. pneumoniae ATCC strain, leading to the production of CR-HvKP transformants. Our results supported that the transformants had drug resistance-related and highly pathogenic phenotypes. Collectively, CR-HvKP OMVs were a type of OMVs co-carrying virulence and antimicrobial-resistant genes to disseminate CR-HvKP.